Status of Copper, Iron and Zinc in Soil, Fodder and Blood Serum of Cattle from Parbhani District of Maharashtra - Singare, P.B.; Meshram, N.A.; Kausadikar, H. K.; Patil, V. D. (Indian Journal of Animal Nutrition, 2023)
The present investigation was carried out to study the mineral status of soil, fodder and blood serum of cattle from Parbhani district of Maharashtra. The total 183 each of soil, sorghum straw and blood serum samples were collected and analyzed for their mineral contents and its significance viz. Cu, Fe and Zn. The results revealed that except DTPA-Zn (88% samples) soils of Parbhani district were found sufficient in DTPA- Cu (100% samples), DTPA- Fe (75 % samples) content whereas, same trend was reflected in case of mineral concentration of straw where 95.7% straw samples were found deficient in total Zn. While other minerals like total Cu (90.71% samples) and total Fe (100% samples) were observed to be sufficient in sorghum straw tested. In case of serum mineral concentration serum Fe (100% samples) and serum Zn (100% samples) were found sufficient while 32% serum samples were found deficient in Cu content. Inconsistent results were observed regarding correlation between mineral contents of soil, straw and blood serum of cattle. Copper and zinc showed positive correlation whereas, iron showed negative correlation between soil and plant. In contrast to plant and serum, all three minerals showed negative correlation. Between soil and serum iron and zinc showed positive correlation whereas, copper showed negative correlation. Based on the results it is concluded that for improvement in production and reproduction efficiency the cattle of Parbhani district need to be supplemented with copper, manganese and zinc by formulating area specific mineral mixture using highly bio-available mineral salt.